Nanocelulose como reforço em filmes de amido para aplicação em embalagens alimentícias - uma revisão - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
This literature review aims to evaluate the efficiency of nanocellulose extracted from plant sources as reinforcement in starch films with different types of starch sources. Considering the concerns about environmental impacts caused by the plastic waste deposit, the literature highlights researches that were carried out with using alternative materials as replacement for synthetic polymers, mainly for applications in food packaging. In this sense, the starch have been highlighted due to its potential to form films, its biodegradable and non-toxic nature, and widely availability in nature. However, they are highly hydrophilic, hence its mechanical and barrier properties need to be improved. In this sense, nanocellulose has been widely studied as reinforcement in starch films and has present good results, especially for mechanical, barrier and thermal properties. In general, scientific literature shows that the mechanical properties of bionanocomposites are improved due to the load transfer from polymeric matrix to the reinforcement, which end up enhancing the tensile strength of the films. Besides that, barrier properties are benefited due to behavior of the starch particles as a physical barrier, as well as the increase of thermal properties after addition of the nanocrystalls.
Keywords: ENGENHARIAS ENGENHARIA DE MATERIAIS E METALURGICA MATERIAIS NAO METALICOS POLIMEROS, APLICACOES; Nanobiocompósitos; Nanocelulose; Celulose nanocristalina; Celulose nanofibrilada